Strategies in the curricular internship in Psychology during pandemia: pathways to the national proposal (Research, Society and Development, 2021)
The present work presents the strategy-building path and the execution of the Psychology internship proposal remotely, developed over the first semester of 2020, at a university in the city of Rio de Janeiro, due to the COVID-19 pandemic. With a qualitative approach, through documentary research on the records of meetings held with academic management, supervisory professors and students, the official documents published by the Ministério da Educação, the Conselho Nacional de Educação, the Conselho Nacional de Saúde, the Conselho Federal de Psicologia and the Associação Brasileira de Ensino de Psicologia, we propose reflections and we expose ethical-political tensions in the initial context of the pandemic and its interfaces with teaching. The construction of proposal for that university was inspired by the National Curriculum Guidelines for undergraduate courses in Psychology and the Fundamental Principles of the Code of Ethics for the Professional Psychologist regarding other activities of the psi professional, such as the preparation of booklets and ebooks, the setting up of a script and podcast recording, circles of conversation. The adaptation of the tasks and the construction of new tasks for the curricular internship in the remote format started to be, for the most part, recommended in a booklet published in August / 2020 by the Associação Brasileira de Ensino de Psicologia and by the Conselho Federal de Psicologia as guidance of internship practices for the second half of 2020 or while the pandemic is in an exceptional state.